One‐step versus two‐step distal self‐expandable metal stent placement: A multicenter prospective randomized trial. Issue 7 (12th January 2021) - Shimizu, Shuya; Naitoh, Itaru; Okumura, Fumihiro; Hirano, Atsuyuki; Miyabe, Katsuyuki; Nishi, Yuji; Takada, Hiroki; Haneda, Kenichi; Anbe, Kaiki; Yoshida, Michihiro; Kondo, Hiromu; Sano, Hitoshi; et al.
Abstract: Background and Aim: Two methods of transpapillary covered self‐expandable metal stent (SEMS) placement are used for distal malignant biliary obstruction (MBO): after initial drainage by plastic stent (two‐step method) and without previous drainage (one‐step method). Methods: In total, 90 patients with unresectable pancreatic cancer and distal MBO were enrolled in this prospective multicenter randomized study and allocated to one‐step ( n  = 45) and two‐step ( n  = 45) groups. The main outcome was the time to recurrent biliary obstruction (TRBO). Secondary outcomes were the rates of early and late adverse events, survival time, the time required for bilirubin level reduction, and cost‐effectiveness. Results: The median TRBO did not differ significantly between the one‐step and two‐step groups (not available vs 314 days, P  = 0.134). SEMS migration occurred significantly more frequently in the two‐step group (14.3% vs 0%, P  = 0.026). No significant difference was observed between groups in early (7.3% vs 14.3%, P  = 0.483) or late (12.2% and 11.9%, P  = 1) adverse events other than RBO, survival time ( P  = 0.104), or the median number of days required to reach a bilirubin level considered to be acceptable for chemotherapy administration (<3 mg/dL; P  = 0.881). The total costs of stent placement and reintervention were significantly lower in the one‐step SEMS group (3347 vs 5465 US dollars, P  < 0.001). Conclusions: The superiority of TRBO with two‐step SEMS placement was not demonstrated. One‐step SEMS placement might be a promising method from the viewpoints of cost‐effectiveness and less invasiveness (UMIN‐CTR clinical trial registration number: UMIN000016010).